Code List Library: A Solution to Improve Research Repeatability, Transparency, and Efficiency by Curating Lists of Clinical Codes. (2018) - Thayer, Daniel; Bown, David; Leake, Thomas; Jones, Jonathan-Lee; Noyce, Richard; Brooks, Caroline; Ford, David
No abstract available